The effect of hydropriming and hormone priming on some physiological and biochemical characteristics in chickpea (Cicer arietinum L.) under salinity stress - Haniyeh Saadat; Mohammad Sedghi (علوم و فناوری بذر ایران)
In order to investigate the effect of hydropriming and hormone priming on some physiological and biochemical characteristics in chickpea under salinity stress a factorial experiment was conducted based on completely randomized design at the University of Mohaghegh Ardabili in 2023 with 3 replications. treatments included four salinity levels (0, 50, 75 and 100 mM) and four levels of priming (control, hydropriming, priming with gibberellin (50 ppm) and salicylic acid (100 ppm)). The results showed that salinity stress reduced germination percentage (GP), germination rate (GR), radicle and Seedling length (RL and SL) But, seed priming improved these traits. Salinity increased the allometric coefficient (AC), So that the highest was observed at (0.860) salinity of 100 Mm. The highest mean daily germination (MDG), plumule length (PL) and total seed protein content were observed in priming with gibberellin and control (without salinity). The maximum DGS (0.144) and MDA (0.0137 mmol/g FW) were related to the treatment with without priming and salinity of 100 mM. The amount of soluble sugars in gibberellin treatment and salinity of 100 mM compared to the control showed an increase about 56%. Also, the use of gibberellin increased amount of proline by about 40% compared to the control (without priming). In general, seed hydropriming, salicylic acid, especially gibberellin